Moderasi Beragama dalam Bernegara di Indonesia - Syarif, Mujar Ibnu; Purkon, Arip (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Religious moderation is an important concept in maintaining harmony and social stability in Indonesia, a country with a very wide diversity of religions and cultures. This study aimed to examined the concept of religious moderation in Indonesia. Using a literature review approach, this paper analyzed various sources of religious moderation literature. The results of the study concluded that religious moderation in Indonesia is driven by several main factors, including the values of Pancasila, the role of religious figures and organizations, and government policies through the Ministry of Religious Affairs. Religious moderation is considered a solution to prevent radicalization, promote tolerance between religious communities, and maintain social cohesion. Religious moderation in Indonesia must continue to be supported by various parties, including the government, community organizations, and religious leaders, through inclusive policies, moderate religious education, and constructive interfaith dialogue.